1970
DOI: 10.1063/1.1659452
|View full text |Cite
|
Sign up to set email alerts
|

Hugoniot Elastic Limit of Single-Crystal Sodium Chloride

Abstract: Single-crystal specimens (7-and 12-mm thick) of sodium chloride were impacted with flat-nosed, gasdriven projectiles, and the Hugoniot elastic limit (HEL) was determined by reducing quartz gauge measurements. The HEL for the [100J, [110J, and [111J crystal directions was 0.26, 0.77, and 7.4 kbar, respectively. Stress-time profiles for specimens shocked in the [100J and [l11J direction show evidence of stress relaxation behind the elastic precursor. This phenomenon is more pronounced in 12-mm-thick specimens. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

1972
1972
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 16 publications
2
10
0
1
Order By: Relevance
“…These measurements are consistent with similar MgO experiments performed by Stevens et al, 43 as well as the elastic-wave particle velocity measurements of other materials. [44][45][46] As shown in Figure 2(a), we do not observe a change in the apparent particle velocity as the elastic wave decays. This suggests that the refractive index of the elastic wave is linear in density or the variation in the refractive index with density is small.…”
Section: B Elastic-plastic Two-wave Structuresupporting
confidence: 53%
“…These measurements are consistent with similar MgO experiments performed by Stevens et al, 43 as well as the elastic-wave particle velocity measurements of other materials. [44][45][46] As shown in Figure 2(a), we do not observe a change in the apparent particle velocity as the elastic wave decays. This suggests that the refractive index of the elastic wave is linear in density or the variation in the refractive index with density is small.…”
Section: B Elastic-plastic Two-wave Structuresupporting
confidence: 53%
“…The value of τ s was slightly larger in acrylic polymer than in the other materials, and τ s increased linearly with flyer thickness. Based on what is known about the shock response of salt, 37,40 such flyer impacts would be expected to produce a steady shock in salt, but in the other target materials the shocks most likely would not have enough time to develop steady-state 45 shock profiles.…”
Section: Energy Transfer From Flyer To Targetmentioning
confidence: 99%
“…The structure of shocks in these four well-characterized materials has been discussed extensively. Shocked salt has a simple fluid-like shock response, 37,40 but the other materials support shocks with more complicated multiple-wave structures. 15,41 Despite the complexity of shocks in the glasses, U p appeared constant in both borosilicate ( Fig.…”
Section: H Fully Supported Shocks In Transparent Targetsmentioning
confidence: 99%
“…1 It is often observed that the elastic-wave front decays with distance and a region of stress relaxation develops behind the elastic-wave front. 2,3 An examination of these structured waves can provide insight into the physical mechanisms governing elastic-plastic deformation and material strength under dynamic loading. [4][5][6][7] For example, past studies on LiF crystals have shown that the elastic wave decays with distance and the decay rate depends on many variables including the crystal orientation, 5 the applied stress, 8 the impurity concentration, 6 and clustering.…”
Section: Introductionmentioning
confidence: 99%